EXPERIMENTAL–DIDACTIC STAND FOR THE ANALYSIS OF INFLUENCE OF THE MAGNETHOREOLOGICAL DAMPER ON THE THRUST FORCE IN SMALL CALIBER ARMS - Marcin BAJKOWSKI; Jacek Mateusz BAJKOWSKI (Scientific Journal of Silesian University of Technology. Series Transport)
This paper presents the laboratory stand, designed for research and didactic purposes. The stand allows investigating the performance of the programmable system for controlling the recoil effect in the small caliber arm–shooter configuration. The system incorporates synchronized magnetorheological (MR) damper. The aim of the study is to describe the influence of the damping of a high-energy pulse from small caliber arm, on the value of the thrust force. For the considered set of MR dampers the range of the operating currents for the MR coil is experimentally selected and adjusted. In the study of the results the emphasis is put on the influence of MR damper on the force characteristics, which directly affects the accuracy of the weapon. The obtained results show that the proposed system special object–MR damper–shooter, has a major, positive effect on the accuracy by reducing the components of the recoil. A scheme of the laboratory stand is presented. Basic parameters of the investigated system and research results are discussed